1998
DOI: 10.1021/ic970577q
|View full text |Cite
|
Sign up to set email alerts
|

Oxorhenium(V) and Oxotechnetium(V) Complexes of Cysteine

Abstract: Earlier attempts to obtain technetium complexes with cysteine always resulted in the formation of a product contaminated with polymeric species. A pure product, which could be chemically characterized and adopted for radiopharmaceutical preparation, has now been obtained by using cystine as the precursor of cysteine. This method has been extended to prepare the corresponding rhenium chelate, isolated as the tetraphenylphosphonium salt [Ph(4)P](+)[{ReO(Cys)(2)}(-){HReO(Cys)(2)}].4H(2)O. The X-ray crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
2
30
0
3
Order By: Relevance
“…[14][15][16][17][18] The Re-Cl(1) distance (2.351(3) Å) is slightly longer than Re-Cl(2) (2.334(2) Å), probably because Cl(1) participates in hydrogen bonding, but both distances are within the accepted range. 57 The Re-NH 2 bond is ∼0.05 Å longer than the Re-N(Im) bond, in agreement with the literature data for complexes with amino acids (mean Re V -N ) 2.188 Å, σ ) 0.032 Å, 20 data) 15,17,18,58 and imidazoles (mean Re V -N ) 2.124 Å, σ ) 0.016 Å, 35 data). [59][60][61][62][63][64] The angles listed in Table S-5 (Supporting Information) show that the octahedron is severely distorted.…”
Section: Oxorhenium(v) Complexesmentioning
confidence: 87%
See 1 more Smart Citation
“…[14][15][16][17][18] The Re-Cl(1) distance (2.351(3) Å) is slightly longer than Re-Cl(2) (2.334(2) Å), probably because Cl(1) participates in hydrogen bonding, but both distances are within the accepted range. 57 The Re-NH 2 bond is ∼0.05 Å longer than the Re-N(Im) bond, in agreement with the literature data for complexes with amino acids (mean Re V -N ) 2.188 Å, σ ) 0.032 Å, 20 data) 15,17,18,58 and imidazoles (mean Re V -N ) 2.124 Å, σ ) 0.016 Å, 35 data). [59][60][61][62][63][64] The angles listed in Table S-5 (Supporting Information) show that the octahedron is severely distorted.…”
Section: Oxorhenium(v) Complexesmentioning
confidence: 87%
“…Less is known about the higher oxidation states. 11,12 Oxorhenium(V)monomerswerepreparedwithcysteine,penicillamine, [13][14][15] and their methyl esters. [16][17][18] Besides the RedO moiety, these compounds contain two ligands, one tridentate-S,N,O and the other bidentate-S,N (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…10 99 Tc-chelate of VII exhibited UV -max at 425 nm and IR stretching bands at 942 cm À1 which were comparable to those of 99 Tc-l-cysteinate (lmax 426 nm and IR band 940 cm À1 ) reported earlier. 10 The reverse phase HPLC retention time of 99 Tc and 99m Tc-l-cysteinate prepared from l-cystine as starting ligands were 5.03 and 5.15 respectively, whereas the 99 Tc and 99m Tc chelates prepared from S-thiomethyl-l-cysteine (VII) exhibited retention times of 5.08 and 5.18, respectively on the same reverse phase HPLC system (Figure 2). Tc-lcysteine under comparable experimental conditions.…”
Section: Mmentioning
confidence: 97%
“…However, this problem could be avoided by using the corresponding disulphide (cystine) as monosulphide precursor; use of large excess of the former produced the above chelate in excellent yield. 10 Therefore it may be concluded that the protection of monosulphide by disulphide formation, which is a useful tool in peptide chemistry, may be successfully applied in thiolate chelation with technetium.…”
Section: à9mentioning
confidence: 99%
See 1 more Smart Citation